Venda direta: a fidelização dos revendedores como estratégia competitiva - Mendes, Bertha Marusa Nunes (2009)
The direct selling industry has a strong ally for the sale and delivery of products and for the recovery of its brand: the work done by its dealers. These professionals are the representatives of these organizations, responsible for creating a link between businesses and end customers. Thus, developing a closer relationship with these resellers can become a strong competitive differential. This research sought to identify, through exploratory research method, the main incentives and the tools more effective than direct selling companies can offer to make their representatives loyalty to the brand. The study was based on responses from dealers who only represent one company and those working with various brands, the so-called multi thus was established the profile of representatives, which allowed the development of assumptions about the levels of loyalty from retailers in relation to the brand they represent, and the most effective tools used by companies selling direct influence for loyalty. The conclusion of this paper presents two effective tools that influence the retention, which are represented by the brand strength and incentives related to the enhancement of personal and professional dealers.